Dendritic cells immunotargeted therapy for atherosclerosis - Zhaohui Li; Yanyan Yang; Jinbao Zong; Bei Zhang; Xiaolu Li; Hongzhao Qi; Tao Yu; Yongxin Li (Acta Pharmaceutica Sinica B)
Atherosclerosis, a chronic inflammatory disease, is markedly influenced by both immune and inflammatory reactions throughout its progression. Dendritic cells, as pivotal antigen-presenting entities, play a crucial role in the initiation of immune responses and the preservation of immunological homeostasis. Accumulating data indicates that dendritic cells are present in healthy arteries and accumulate significantly in atherosclerotic plaques. Novel immunotherapeutic approaches and vaccination protocols have yielded substantial clinical advancements in managing chronic inflammatory diseases, with dendritic cell-centric modalities emerging for atherosclerotic management. In this review, we delineate the essential functions and underlying mechanisms of dendritic cells and their subsets in the modulation of atherosclerotic inflammation and immune responses. We underscore the immense promise of dendritic cell-based immunotherapeutic strategies, including vaccines and innovative combinations with nanotechnological drug delivery platforms for atherosclerosis treatment. We also discuss the challenges associated with dendritic cell immunotherapy and provide perspectives on the future direction of this field.